New Thiodiketopiperazine and 3,4-Dihydroisocoumarin Derivatives from the Marine-Derived Fungus Aspergillus terreus - Jing-Shuai Wu; Xiao-Hui Shi; Guang-Shan Yao; Chang-Lun Shao; Xiu-Mei Fu; Xiu-Li Zhang; Hua-Shi Guan; Chang-Yun Wang (Marine Drugs, 2020)
Aspergillus terreus has been reported to produce many secondary metabolites that exhibit potential bioactivities, such as antibiotic, hypoglycemic, and lipid-lowering activities. In the present study, two new thiodiketopiperazines, emestrins L (1) and M (2), together with five known analogues (3−7), and five known dihydroisocoumarins (8−12), were obtained from the marine-derived fungus Aspergillus terreus RA2905. The structures of the new compounds were elucidated by analysis of the comprehensive spectroscopic data, including high-resolution electrospray ionization mass spectrometry (HRESIMS), one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR), and electronic circular dichroism (ECD) data. This is the first time that the spectroscopic data of compounds 3, 8, and 9 have been reported. Compound 3 displayed antibacterial activity against Pseudomonas aeruginosa (minimum inhibitory concentration (MIC) = 32 μg/mL) and antifungal activity against Candida albicans (MIC = 32 μg/mL). In addition, compound 3 exhibited an inhibitory effect on protein tyrosine phosphatase 1 B (PTP1B), an important hypoglycemic target, with an inhibitory concentration (IC)50 value of 12.25 μM.